Development of “AMICO” website as a media of non-judgemental expression for youth - Skolastika Hapsari; Nathania Pramendra Yaslim; Eva Anita Sarereake; Nadia Natasya (Education and Social Sciences Review, 2022)
Everyone has problems and complaints that they faces. However, not everyone can easily share their complaints and feelings with others because of various factors that bother them. AMICO is an interactive website that the author created to help those who want to share their problems and even their works in a forum that allows anonymity. This study aims to see how much young people are interested in using AMICO and the impression they give after using AMICO. In this study using a quantitative approach and using the method of action. Data retrieval was carried out using a Google Form containing questions about the Amico website itself, both from the features provided, the design used, and others. The distribution of Google Forms is carried out via Internet Relay Chat (WhatsApp) and social media (Instagram). The number of respondents was 35 people with an age range of 15 to 25 years. The results showed that most of the testees considered the AMICO website to be innovative and Amico is a good medium of sharing their issues and their works.